Strategies to overcome the side effects of chimeric antigen receptor T cell therapy. Issue 1 (4th January 2022) - Mirzaee Godarzee, Mohadeseh; Mahmud Hussen, Bashdar; Razmara, Ehsan; Hakak‐Zargar, Benyamin; Mohajerani, Fatemeh; Dabiri, Hamed; Fatih Rasul, Mohammed; Ghazimoradi, Mohammad Hossein; Babashah, Sadegh; Sadeghizadeh, Majid
Abstract: Chimeric antigen receptor (CAR) therapy is a method directing T lymphocytes against antigens on the surface of tumors, increasing target cell elimination. Genetic engineering enhances the capability of immune cells to detect new antigens expressed on cell surfaces. CAR T cell therapy is a significant breakthrough for treating human malignancies; however, different side effects (e.g., cytokine release syndrome) restrict its application. Improving design and using various combined receptors enhance the performance of these cells. This review discusses limitations and risk factors associated with CAR T cell therapy. We also review some alternative approaches for developing the next generation of CAR T cells. Abstract : This review discusses some limitations, side effects, and risk factors associated with chimeric antigen receptor (CAR) T cell therapy and provides strategies to address them. We also introduce some alternative approaches for developing the next generation of these engineered cells.